Exploring Islamic retailer store attributes from consumers perspectives: an empirical investigation - Hashim, Haslinda; Hussin, Siti Rahayu; Zainal, Nurdiyana Nadihah (Faculty of Economics and Management, Universiti Putra Malaysia, 2014)
Retailers’ interest in using various combinations of store attributes to form an Islamic retail mix and project their image as an Islamic store is significantly increasing. This is due to the fact that scholars and practitioners are aware of the increasing purchasing power and significant size of the Muslim consumer segment. A review of the literature reveals that most studies conceptually and theoretically examined the principles and elements that constitute an Islamic marketing mix or retail mix. The purpose of this study is to empirically examine the stores’ attributes and how they reflect an Islamic retailer from the perspective of Muslim consumers. Data were collected through a self-administered questionnaire consisting of 300 consumers from shopping malls in Kuala Lumpur, Malaysia. Factor analysis indicated various store attributes correlate to reveal four dimensions of an Islamic retailer which are Trustworthy Pricing, Conforming Store Atmosphere, Trustworthy Product and Ethical Promotion.